Reptile community responses to native and non‐native riparian forests and disturbance along two rivers in Arizona. (10th January 2020) - Bateman, Heather L.; Riddle, Sidney B.
Abstract: Aridland riparian forests are undergoing compositional changes in vegetation and wildlife communities due to altered hydrology. As flows have been modified, woody vegetation has shifted from native‐tree dominated to non‐native and shrub encroached habitats. Squamate vertebrates such as lizards and snakes are important food web links in riparian ecosystems of the Sonoran Desert. However, little is known about how these communities might respond as riparian forests transition from native tree dominated habitats to open xeroriparian woodlands. We used pitfall arrays deployed across three types of riparian forest to document reptile community patterns, measure vegetation, and produce species‐habitat models. Riparian forests differed on the basis of habitat composition and physiognomy. Two types, cottonwood‐willow ( Populus‐Salix ) and mesquite ( Prosopis ) stands, were characterized by high woody species richness. The third type, non‐native saltcedar ( Tamarix ) stands, had high densities of woody debris and greater canopy coverage. Results show that lizards were common and abundances greatest in cottonwood‐willow, especially for arboreal species. Species‐habitat models for three of five lizard species indicated a negative association to saltcedar‐invaded habitat and no species appeared to select saltcedar‐dominated habitat. Mesquite was an intermediate habitat between upland and riparian, and supports high species diversity. A wildfire in the cottonwood‐willow forest disproportionately affected abundance of ground‐foraging whiptail ( Aspidoscelis ) lizards; whereas, abundance of arboreal spiny ( Sceloporus ) species was unchanged. Expected drivers from climate and water use could transition cottonwood forests to other woody‐dominated types. Our results suggest that mesquite woodlands would provide higher quality habitat for riparian reptiles compared to non‐native saltcedar stands.